2021
DOI: 10.1186/s12903-021-01764-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life among a group of patients with substance use disorders in rehabilitation treatment: a cross-sectional study

Abstract: Background Little is known about the effect of illicit drugs on oral health-related quality of life. Our aim was to investigate oral health-related quality among patients with substance use disorders, and its association with dental caries experience and drug use profile. Methods Applying a stratified cluster random sampling method, we conducted a cross-sectional study on 267 in-treatment patients with substance use disorders in Isfahan, Iran in 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…In daily activities, the prevalence of OHIP is most disturbed, namely difficulty eating. 27 The results of this study were similar to those of Astrom et al which showed that the OHRQoL of respondents who were undergoing rehabilitation were mostly poor. The most adverse effects experienced were difficulty eating and sleeping or being in a relaxed state.…”
Section: Discussionsupporting
confidence: 90%
“…In daily activities, the prevalence of OHIP is most disturbed, namely difficulty eating. 27 The results of this study were similar to those of Astrom et al which showed that the OHRQoL of respondents who were undergoing rehabilitation were mostly poor. The most adverse effects experienced were difficulty eating and sleeping or being in a relaxed state.…”
Section: Discussionsupporting
confidence: 90%
“…There is also an increased risk in oral health problems among people who have an AOD dependence, which can also affect quality of life [ 12 , 13 , 14 , 15 ]. Amiri and Shekarchizadeh [ 16 ] also found that among people receiving inpatient treatment for AOD dependence, oral health problems had an impact on eating, speaking, sleeping, going out, relaxing, smoking, emotional stability and affected their contact with other people.…”
Section: Introductionmentioning
confidence: 99%
“…There is little argument that poor oral health is a significant problem among clients of AOD services [1]; and that good oral health is an integral part of overall health, quality of life and wellbeing [2]. Studies have shown that people who use drugs are at increased risk of poor oral health [3] that impacts on their quality of life [2,[4][5][6]. As described in the scoping review, studies of people with substance use disorder (SUD) report high rates of caries, periodontal disease, xerostomia (dry mouth), bruxism, prostheses, toothache and tooth loss [7].…”
mentioning
confidence: 99%